Antinomianism and Professionalism in Media Practice: Do Ethics Still Matter? - Nwokeocha Ifeanyi Martins (CV. Rayyan Dwi Bharata, 2023)
Ethics is very important aspect of any profession because it helps the practitioner to judge his/her actions. In other words, it makes it possible for us to subject our conscience to test. It is socially determined, but individually enforced. In other words, antinomian is the opposite of the legalistic principle subscriber. They are those that believe that man should not be pinned down or pigeon holed into any particular way of life in the name of a written code. Therefore, the study seeks to antinomianism and professionalism in media practice: Do ethical codes still matter? The study examined all concepts and critical reviews were given to support to the study. The study employed library based research method and social responsibility theory was used to provide the theoretical background of the study. The study recommended that Since journalism practice is based on accuracy, fairness, trust, honestly among others, journalists should follow and abide by the ethical codes in other to lead them on the right part; antinomianism is not the best because it leads journalist to corruption, so journalist should stick to the ethical codes.